2022
DOI: 10.1038/s41598-022-16023-7
|View full text |Cite
|
Sign up to set email alerts
|

Fate of hips complicated by avascular necrosis of the femoral head following reconstructive surgery in nonambulatory patients with cerebral palsy

Abstract: The purpose of this study was to evaluate the influence of avascular necrosis of the femoral head (AVN) following hip reconstructions on the future hip development of cerebral palsy (CP) patients. A retrospective study of 394 hips in 205 nonambulatory patients with spastic CP who underwent reconstructive hip surgery was performed. The mean age at surgery was 7.3 ± 2.4 years. The mean follow-up duration was 5.6 ± 2.7 years, and the mean age at the latest follow-up was 12.8 ± 3.4 years. AVN was classified in ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 44 publications
(48 reference statements)
0
4
0
Order By: Relevance
“…There are many cohort studies which report a high success rate in terms of improved hip morphology at medium- to long-term follow-up. However, many studies report high rates of complications including mortality [ 28 , 29 , 62 , 63 , 64 , 65 , 66 ]. In one study, the mortality rate was 4% and the overall complication rate was 25%, rising to 68% in children with gastrostomies or tracheostomies [ 62 ].…”
Section: Bony Reconstructive Surgery For Cphdmentioning
confidence: 99%
See 2 more Smart Citations
“…There are many cohort studies which report a high success rate in terms of improved hip morphology at medium- to long-term follow-up. However, many studies report high rates of complications including mortality [ 28 , 29 , 62 , 63 , 64 , 65 , 66 ]. In one study, the mortality rate was 4% and the overall complication rate was 25%, rising to 68% in children with gastrostomies or tracheostomies [ 62 ].…”
Section: Bony Reconstructive Surgery For Cphdmentioning
confidence: 99%
“…Recurrent hip displacement and avascular necrosis are two of the most disappointing late outcomes after reconstructive surgery [ 28 , 62 , 63 , 64 , 65 , 66 ]. Earlier studies of AVN after hip reconstruction in children with CP used or adapted the classifications for AVN in DDH [ 64 , 65 ].…”
Section: Bony Reconstructive Surgery For Cphdmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown how hip surveillance programs improve the outcome of HD in terms of rate of dislocated hips and salvage surgery [ 18 , 34 , 35 ]. However, this strategy may be difficult to pursue in some cases given the fragility and/or the limited life expectancy of many of these patients [ 36 ], the need for invasive surgery even in asymptomatic children with the possibility of parental refusal, the high rate of complications after hip surgery [ 37 , 38 , 39 , 40 ], and the frequent need for repeated surgeries before reaching skeletal maturity [ 31 ]. Moreover, an older age at the time of reconstructive surgery is associated with a reduced need for surgical revision [ 41 ].…”
Section: Discussionmentioning
confidence: 99%